Migraine and vascular risk factors in the elderly. Issue 1 (6th May 2013) - Gilad, Ronit; Boaz, Mona; Dabby, Ron; Finkelstein, Vitali; Rapoport, Abraham; Lampl, Yair
<x xml:space="preserve">Abstract</x> Aim The association between migraine and cerebrovascular disease is well documented in younger migraine patients, especially those with aura. Prevalence estimates of vascular risk factors among elderly migraine sufferers are lacking. The present study was designed to estimate the prevalence of vascular risk factors in the elderly population with late onset of migraine without aura. Methods The medical records of 163 patients aged 50 years and older suffering from migraine without aura were assessed for vascular risk factors, including hypertension, elevated serum lipid levels, diabetes mellitus and cardiovascular disease. Prevalence was estimated and compared with age‐ and sex‐matched vascular risk factor estimates for the general population extracted from the 2003–2004 Israeli National Health Interview Survey, and to a group of patients matched by age suffering from migraine with aura. Results Among women with migraine without aura, hypertension, hyperlipidemia and diabetes mellitus were significantly less prevalent than among women without migraine without aura. Prevalence estimates for vascular risk factors did not differ by migraine among males. The group of older patients suffering from migraine with aura showed a higher incidence of vascular risk factors in respect to the group of migraine patients without aura. Conclusions The findings of the present study might have an important clinical relevance, suggesting another pathophysiological process in respect to patients suffering from migraine with aura, and this evidence might have different therapeutic implications. Geriatr Gerontol Int 2014; 14: 220–225.